Kegiatan Pabrikasi Mesin Giling Kopi Kering Merek BEJE Tipe GLK 20 di PT Bahagia Jaya Sejahtera: Construction Activities of BEJE GLK 20 Type Dry Coffee Grinding Machine at PT Bahagia Jaya Sejahtera - Rifky Wildan Muhammad; Titis Pury Purboningtyas; Eka Widiono; Tohari Tohari (Politeknik Pertanian Bogor, 2021)
The development of coffee production needs to be supported by technological readiness, so that appropriate agricultural tools and machines (alsintan) are needed in the post-harvest processing of coffee. This study aims to identify the design drawing of a dry coffee grinder, produce a dry coffee grinder, and perform a performance test of the BEJE GLK 20 type dry coffee grinder. The research method used is a qualitative approach using a description method that explores and examines in depth the process activities. dry coffee grinder production. The manufacturing process for the dry coffee grinding machine has been successfully carried out by following the design that has been made and the stages in accordance with the machine design rules. The results of the dry coffee grinding power analysis with a power of 0.835 kW (1.12 HP) obtained a coffee grinder tooth capacity of 8.76 kg/hour from a total output capacity of 58.2 kg/hour.